A mode of space production in the nineteenth century :|İcadiye neighborhood as a case of ifraz - Arıkan, Burcu. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2021., 2021)
This thesis deals with a specific method of space production which is called ifraz. Ifraz means dividing a larger piece of land into smaller, and this method may be implemented in various ways depending on the context. This study will focus on parceling empty suburban areas to commodify nature and sell and transform agricultural forests, gardens, and yards into built areas. I will briefly demonstrate the literature on urban history, land, property, and infrastructure to base my findings on ifraz and urbanization. Through a more extensive set of the archival scan, ifraz, in general, will be demonstrated as an intensified type of space production in the nineteenth century, accelerating significantly with the Tanzimat Edict. Then, a detailed analysis of Icadiye Neighborhood as the case study will present a specific model of urbanization via the commodification of empty suburban landscapes. Icadiye is also important in terms of being an Armenian neighborhood. Both demonstrate specific features of nineteenth-century urbanization and the continuum of an urban sprawl dating back to the seventeenth century; Icadiye will contribute to the discussions on center/ periphery, urban/ suburban distinctions. In the general context, I will expand Islamic city conception and approaches detached from the dynamics of capitalism in urban historiography to raise new questions, and ifraz in a broader sense, has great potentials for further studies.
Keywords: Turkey -- Social life and customs.